Establishing Good Samaritan programs in healthcare institutions: a method for enhancing patient experiences and increasing loyalty - James K. Elrod; John L. Fortenberry (BMC, 2018)
Abstract Background Healthcare institutions deliver essential services that practically everyone needs at least periodically over the course of their lives. Hospital admissions, in particular, place patients in circumstances very foreign to them, with uncertain outcomes often being the case, causing stress for care recipients and their loved ones. Health and medical establishments must be very mindful of this and work toward supplying environments that are as comforting as possible for those in their care. Discussion One avenue for relieving patients and their loved ones of hardships that complicate already difficult situations involves the development and implementation of Good Samaritan programs. Termed in reference to the biblical Good Samaritan who attended to the physical and emotional needs of his neighbor, these programs supply aid and comfort over and above that which traditionally has been delivered to patients in healthcare delivery settings, fostering satisfaction, positive word-of-mouth communications, and loyalty. Willis-Knighton Health System operates a Good Samaritan program, notably including a patient concierge team, complimentary lodging, and free transportation, with the offering greatly improving the patient experience. This article profiles Willis-Knighton Health System's Good Samaritan program and supplies a blueprint for establishing similar offerings in virtually any healthcare entity. Conclusions Good Samaritan programs provide significant support and assistance to care recipients and their loved ones at particularly difficult times. Willis-Knighton Health System has observed firsthand the many benefits afforded by its Good Samaritan program, relieving those served by the establishment of many burdens and endearing them to the institution for its associated investments which foster peace of mind.